Pengembangan Multimedia Interaktif pada Pembelajaran Geometri - Rahmatullah Bin Arsyad; Muhammad Fathurrahman; Muhammad Syahrul Kahar; Arie Anang Setyo; Nika Fetria Trisnawati (Universitas Muhammadiyah Sorong, 2022)
This research is a development study with the aim of determining the feasibility of geometric interactive media that is carried out in students of SMA AL-Amin Kota Sorong and evaluating the effectiveness of interactive multimedia based on the opinions of linguists, media specialists, and material experts. The four steps of the development process are the defining stage (define), the design stage (design), the development stage (develop), and the deployment stage. This development model is called the 4-D device development model (Four D Model) (disseminate). Linguists, subject matter experts, and media specialists were contacted about and evaluated the interactive multimedia that had been developed. The subject matter in Interactive Multimedia is related to geometry. According to the assessment of linguists in the development of multimedia learning, this study has succeeded in developing multimedia interactive geometry that has a very decent quality with an average of 3.7, while in the assessment of material experts obtained an average assessment of 3.6 and based on media experts, this study has obtained an average score of 3.5 which is categorized so that based on the assessment criteria, interactive multimedia meets the eligibility criteria